2022
DOI: 10.1111/jopr.13600
|View full text |Cite
|
Sign up to set email alerts
|

Implants in the pterygoid region: An updated systematic review of modern roughened surface implants

Abstract: Purpose To determine the survival rates of modern roughened surface dental implants in the pterygoid region. Methods This systematic review was an update from a previously published systematic review in 2011, which largely reported data on older machined surface dental implants. An electronic search for articles in the English language literature published from January 1, 2010 to December 8, 2021 was performed using PubMed, Scopus, and CENTRAL search engines. After applying a systematic search process in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…A previous systematic review on the placement of dental implants in the maxillary tuberosity estimated a 94.6% implant cumulative survival rate with a follow-up up to 14 years [21]. A recent systematic review assessing the outcome of implants in the pterygoid region estimated a 95.5% implant cumulative survival rate at 6 years of follow-up [22]. As illustrated by the results, both these treatment modalities are viable with predictable outcomes, offering the surgical advantage of a virtual impossibility of implant insertion in the posterior region of the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review on the placement of dental implants in the maxillary tuberosity estimated a 94.6% implant cumulative survival rate with a follow-up up to 14 years [21]. A recent systematic review assessing the outcome of implants in the pterygoid region estimated a 95.5% implant cumulative survival rate at 6 years of follow-up [22]. As illustrated by the results, both these treatment modalities are viable with predictable outcomes, offering the surgical advantage of a virtual impossibility of implant insertion in the posterior region of the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…In another systematic review on 1983 PIs in 634 patients, a mean survival rate of 94.87% was reported [ 42 ]. Bidra et al [ 9 ] reported a 95.5% cumulative survival rate of PIs after 6 years. Recently, a FEA study on PIs was also published [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are no guarantees of complete healing and predictable recovery of the alveolar bone, and complications have also been reported, primarily including sinusitis. Alternatively, several surgical and reconstructive techniques have been proposed, such as inlay/onlay grafts and dental implants, guided bone regeneration (GBR), distraction osteogenesis, splitting of the alveolar ridge, Lefort I interpositional grafts, use of inclined implants, zygomatic implants, and pterygoid implants [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations